Smoke Particle, Polycyclic Aromatic Hydrocarbons and Total Benzo[a]pyrene Toxic Equivalence Emitted by Palm Oil Sewage Sludge Bio-Char Combustion - Wachara Kalasee; Panya Dangwilailux (Applied Sciences, 2021)
The size distribution, total particle mass concentration (TPMC), polycyclic aromatic hydrocarbons (PAHs) value, and total Benzo[a]pyrene Toxic Equivalence (BaPTE) concentration of smoke particles from palm oil sewage sludge (POSS) bio-char combustion were studied. In this experiment, temperature data of the POSS bio-char combustion were recorded in two parts: particle temperature (Tp) by using a two-color pyrometer and temperature at 300, 500 and 800 mm, respectively, above the fire base by using K-type thermocouples. The POSS bio-char moisture content, clean air speed values, and burning period affected the change of temperature above the fire base. The mass median aerodynamic diameter (MMAD) values of the POSS bio-char combustion were found to be 0.44 to 1.05 micron at various moisture contents and burning periods. The MMAD, TPMC, and PAHs values increased with increasing moisture content and decreased the POSS bio-char combustion period. For the total BaPTE values, the results showed that the decrease in moisture content of the POSS bio-char samples had a prime influence in decreasing the total BaPTE values. Meanwhile, with decreases in the clean air speed values, the total BaPTE values were increased. Comparing the total BaPTE data between the experimental results and predicted values, the first-degree model had a better fit in predicting than the zero-degree model; this result was confirmed by the higher mean of the coefficient of determination.
Keywords: Thermochemical Biomass Conversion Processes; Fire dynamics and safety research; Energy and Environment Impacts